Electrical properties of perovskite solar cells by illumination intensity and temperature‐dependent photoluminescence imaging. (20th October 2021) - Bui, Anh Dinh; Mozaffari, Naeimeh; Truong, Thien N.; Duong, The; Weber, Klaus J.; White, Thomas P.; Catchpole, Kylie R.; Macdonald, Daniel; Nguyen, Hieu T.
Abstract: Hybrid organic–inorganic perovskite solar cells (PSCs) are one of the most promising candidates for next generation photovoltaics. Further improvement in their performance, particularly efficiency, durability and reproducibility, requires a deep understanding of recombination losses during fabrication and within a device itself. In this work, we report a contactless, imaging‐based procedure to spatially resolve electronic properties of PSCs including implied open‐circuit voltage ( iV oc ) and its temperature coefficient, ideality factor ( n id ) and activation energy of recombination ( E A ) by employing illumination intensity and temperature‐dependent photoluminescence. The illumination intensity dependence of iV oc allows the extraction of n id whereas its temperature dependence allows the extraction of the temperature coefficient and E A . This imaging approach is then applied to investigate changes of these electronic parameters on fully and partially fabricated devices. Abstract : Illumination intensity and temperature dependent photoluminescence are employed to image open‐circuit voltage, ideality factor, and activation energy of recombination of perovskite‐based photovoltaic devices. These methods could be used to quantify the cell performance of finished and partially finished solar cells at as‐prepared and degraded states. They also allow monitoring of the reproducibility of the cell fabrication process.